Chronic Drug-Induced Liver Injury: Updates and Future Challenges - Wang, Qiaoling; Huang, Ang; Wang, Jia-Bo; Zou, Zhengsheng (Frontiers in Pharmacology, 2021)
Chronic drug-induced liver injury (DILI), defined as DILI with persistent liver injury more than one year after the first onset by the latest European guidelines, is a notable challenge globally with big issues of defining causality and establishing effective treatment. About 20% of patients with DILI develop into chronic DILI. Chronic DILI manifests as persistent or repeated inflammatory or diminishing bile ducts, even progresses to cirrhosis and needs liver transplantation eventually. However, research on chronic DILI over the last decades is still lacking, and the incidence, phenotypes, mechanisms, risk factors, and treatment have not been fully understood. In this paper, we reviewed the definition of chronic DILI, updated clinical studies in terms of incidence, special manifestations, and promising risk factors of chronic DILI, along with the recent progress and challenges in glucocorticoid therapy.